Performance of Modified Slow Sand Filter to Reduce Turbidity, Total Suspended Solids, and Iron in River Water as Water Treatment in Disaster Areas - Fitriani, Nurina; Wahyudianto, Febri Eko; Salsabila, Nada Fikna; Mohamed, Radin Maya Saphira Radin; Kurniawan, Setyo Budi (2023)
This study aimed to determine the ability to modify slow sand filter (SSF) media with silica sand or Anadara granosa shells on the efficiency of removal of turbidity, total suspended solids (TSS), and iron in the water of Kali Jagir Surabaya as an effort to achieve clean water in disaster areas, to obtain the influence of variables, and to optimize the obtained results. The research data was processed using Design Expert 11 Software which fac¬tors consisted of media type, filtering speed, and running time, for the responses of removal efficiencies for each parameter. The reactor was operated continuously for 6 days, and samples were analyzed for turbidity parameters based on Indonesian standard (SNI 06-6989.25-2005); TSS and Iron Standard Method 23rd 3500A. In addition, the results of the parameters were processed using the Analysis of Variance (ANOVA) to show the significant effect of the variables on the efficiency of the elimination of all parameters. Optimal research was achieved in the SSF reac¬tor unit with silica sand media type and filtering speed of 0.1 m/hour turbidity removal efficiency of 82.07%; TSS 89.5%; and 50.14% iron. However, the reactor that was chosen was the filtering speed of 0.1 m/hour with a flow rate of 22.8 L/day, while the SSF was suitable to be applied in disaster areas, which had a large discharge. Hence, the reactor is suitable for use in water sanitation in disaster areas, namely with a filtering speed of 0.3 m/hour which produces a discharge of 68.4 L/day with variations of sand, geotextile, and silica sand media.